Biogas Production from Agave durangensis Mezcal Bagasse Pretreated Using Chemical Processes - Refugio Hernández-López; Iván Moreno-Andrade; Blanca E. Barragán-Huerta; Edson B. Estrada-Arriaga; Marco A. Garzón-Zúñiga (Fermentation)
This study evaluated the viability of using the solid residues (bagasse) of the mezcal industry produced with Agave durangensis as a substrate for biogas production, using two chemical pretreatments, acid (HCl) and alkaline (KOH + Ca(OH)2), to enhance its biodegradability and improve the anaerobic digestion (AD) process. The chemical composition of bagasse was analyzed before and after the chemical pretreatments and then AD experiments were conducted in anaerobic sequential batch reactors (A-SBR) to analyze the effect of pretreatments on biogas production performance. The results showed that acid pretreatment increased cellulose content to 0.606 g, which represented an increase of 34%, and significantly reduced hemicellulose. In contrast, alkaline pretreatment did not show significant changes in cellulose composition, although it caused a swelling of the Agave durangensis mezcal bagasse (Ad-MB) fibers. In terms of biogas production, Ad-MB pretreated with acid (Ad-MB-acid) increased cumulative production by 76% compared to the Agave durangensis mezcal bagasse that was not pretreated (Ad-MB-not pretreated) and by 135% compared to Agave durangensis mezcal bagasse pretreated with an alkaline solution (Ad-MB-alkaline). These results confirmed that Agave durangensis solid waste from the mezcal industry that receives acidic chemical pretreatment has the potential to generate biogas as a sustainable biofuel that can be used to reduce the ecological footprint of this industry.